Ovine leptospirosis in Brazil - Lucheis, S. B. (2011)
Leptospirosis is a zoonosis distributed worldwide, endemic mainly in humid subtropical and tropical countries, with epidemic potential. It affects a range of both wild and domestic animals, including sheep, which transport leptospires in their urine and, therefore, can infect other animals and humans who deal with them. Therefore, leptospirosis is characterized as an occupational zoonosis. In individual herds leptospirosis can cause severe economic loss due to miscarriages and outbreaks of mastitis with a significant reduction of milk production. The disease is caused by Leptospira interrogans, which was reclassified into 13 pathogenic species, and distributed into more than 260 serovars classified into 23 serogroups. The clinical signs of infection may vary depending on the serovar and host. In maintenance hosts, antibody production is generally low; there are relatively mild signs of the disease, and a prolonged carrier state with organisms in the kidneys. In incidental hosts, the disease may be more severe, with high titers of circulating antibodies and a very short or nonexistent renal carrier state. In general, young animals with renal and hepatic failure have more serious infections than adults. Several diseases may produce symptoms similar to those of leptospirosis, so that laboratory confirmation, through microscopic agglutination test, for example, is required. The effectiveness of treatment depends on early diagnosis and appropriate therapy, depending on clinical features, since leptospirosis can develop into chronic liver disease and nephropathy, progressing towards death. Improvements in habitation and sanitary conditions, rodent control, vaccination, isolation and treatment of affected animals are the main measures for the control of leptospirosis.